2015
DOI: 10.1016/j.socscimed.2015.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Educational trajectories after childhood cancer: When illness experience matters

Abstract: With the increase in survival from childhood cancer, research has increasingly focused on the educational and professional achievements of childhood cancer survivors. Yet, if large-scale studies provide an acute description of the current situation of childhood cancer survivors, little is known about their trajectories and the social processes shaping these trajectories. Using a qualitative methodology, drawing from a life course perspective, this study sought to describe the role of childhood cancer and its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
1
12
0
6
Order By: Relevance
“…Different mechanisms between men and women in the selection of a career could partly explain this finding, as suggested by a qualitative study based on 80 interviews with childhood cancer survivors randomly selected from the French cohort. In this study, 16% of male survivors said they had disregarded a typically blue-collar career choice during adolescence or young adulthood and had chosen an educational path leading to white-collar occupations, because of physical sequelae, or because of concerns about their future health, as compared with 5% of females ( Dumas et al , 2015 ).…”
Section: Discussionmentioning
confidence: 80%
“…Different mechanisms between men and women in the selection of a career could partly explain this finding, as suggested by a qualitative study based on 80 interviews with childhood cancer survivors randomly selected from the French cohort. In this study, 16% of male survivors said they had disregarded a typically blue-collar career choice during adolescence or young adulthood and had chosen an educational path leading to white-collar occupations, because of physical sequelae, or because of concerns about their future health, as compared with 5% of females ( Dumas et al , 2015 ).…”
Section: Discussionmentioning
confidence: 80%
“…For example, in a qualitative French study, young female cancer survivors had lower educational attainment than expected but often chose occupations in child care or healthcare, which fulfilled their desire to reciprocate the care they had received. 35 Future longitudinal studies should aim to acquire more holistic understanding of the issues influencing educational and vocational pathways, the transition from education to employment after cancer during the AYA years, and effective interventions that facilitate the return to school and work after cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the effect on the patient illness experience was positively associated with female gender and negatively associated with age, socioeconomic status, and education level. The effects of age and gender differences on the trajectories of individual illness experiences have been widely recognized, with most analyses showing a greater reactivity of women and younger subjects [ 32 37 ]. Discrepancies in the illness experience related to socioeconomic, racial, and cultural factors were also reported in a number of pathophysiological conditions [ 38 43 ].…”
Section: Discussionmentioning
confidence: 99%